Impact of Changes on Agricultural Patterns in South Haryana, India - Vinita; Yadav, Sunita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The agricultural sector of southern Haryana has witnessed extensive and profound changes over the past few decades. These changes are not limited to crop rotations and irrigation systems, but have also significantly altered agricultural techniques, mechanization, fertilizer use, and socio-economic practices. The traditional wheat-millet-based rain-fed agricultural system has been replaced by a multi-cropping system of cash crops and vegetables. Climate change, rainfall uncertainty, and government agricultural diversification policies have driven farmers to shift to water-efficient and high-value crops. Modern irrigation technologies, such as micro-irrigation, solar-powered pumps, and check dams, have increased water use efficiency and productivity. Significant progress has also been made in agricultural mechanization, which has accelerated and modernized the production process while addressing labor shortages. However, this has led to changes in the rural labor structure, particularly affecting women workers. Climate change has adversely affected crop rotations and production through temperature increases, rainfall volatility, and water table declines. Various government schemes, such as the PMKSY, the National Mission on Sustainable Agriculture, and the Kusum Yojana, have played a significant role in promoting modern agricultural practices. Changes in market structures and consumer behavior have increased demand for vegetables, fruits, and organic products, prompting farmers to shift to more profitable crops. Technological innovations, such as drones, mobile apps, soil health cards, and hydroponics, have given a new direction to the agricultural sector, although the spread of these technologies remains limited to small farmers. Socio-cultural changes—such as the migration of youth from agriculture, increased participation of women, and the rise of farmer producer organizations—have profoundly impacted the agricultural landscape. Overall, this transformation in agriculture in South Haryana is the result of a combined impact of economic, environmental, policy, technological, and social factors, which will further alter the direction of regional agriculture in the future.